COUNSELING ON THE PREPARATION OF FINANCIAL REPORTS AS A FORM OF EMPOWERMENT FOR MSMEs IN THE CITY OF PEMATANG SIANTAR - Christine Loist; Loist Abdi Putra; Marthin Hutler Ambarita; Boo Wang; Uppaliry Suma (Glow: Jurnal Pengabdian Kepada Masyarakat, 2023)
The city of Pematangsiantar also has industrial sectors, both small, medium and even large scale, and trade centers, both traditional and modern markets. The results of the initial survey found in the field when conducting research on the community beforehand, illustrated that several business actors who were categorized as MSMEs had not been systematically recorded so that problems that occurred in the field such as the lack of knowledge of business actors on how to grow their businesses, difficulty distributing products, lack of innovation products, lack of branding and lack of optimal online marketing cannot be optimally addressed because there is no real data available regarding the number of business actors, especially those categorized as MSMEs. The implementation method uses the Participatory Rural Appraisal (PRA) model which emphasizes community involvement in all activities starting from planning, implementing, and evaluating program activities. In accordance with the results of interviews after the implementation of community service activities, it is known that the understanding of MSME actors regarding the preparation of financial reports has increased by 90%. Counseling on the preparation of financial reports as a form of empowerment for MSMEs in Pematang Siantar City is one of the efforts to improve the quality of MSMEs and encourage economic growth in Pematang Siantar City.